2017
DOI: 10.1364/optica.4.001344
|View full text |Cite
|
Sign up to set email alerts
|

Efficient picosecond x-ray pulse generation from plasmas in the radiation dominated regime

Abstract: The efficient conversion of optical laser light into bright ultrafast x-ray pulses in laser created plasmas is of high interest for dense plasma physics studies, material science, and other fields. However, the rapid hydrodynamic expansion that cools hot plasmas has limited the x-ray conversion efficiency (CE) to 1% or less. Here we demonstrate more than one order of magnitude increase in picosecond x-ray CE by tailoring near solid density plasmas to achieve a large radiative to hydrodynamic energy loss rate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 27 publications
(46 reference statements)
0
27
1
Order By: Relevance
“…Thus, a delay between the maximum of the laser pulse and maximum of the K-shell radiation is expected as it is demonstrated in Fig.5. Therefore, we conclude that the high density and temperature of plasma, dynamically changing at sub-picosecond time scale, in combination with (dynamically changing) effects of opacity are determining the femtosecond duration of the Xray line emission in contrast to picosecond duration estimated from assumptions of optically thin plasma under steady state conditions [39]. Finally, simulations were carried out for spectra measured from a polished Si wafer to understand the differences in the emission for different morphologies of the samples.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, a delay between the maximum of the laser pulse and maximum of the K-shell radiation is expected as it is demonstrated in Fig.5. Therefore, we conclude that the high density and temperature of plasma, dynamically changing at sub-picosecond time scale, in combination with (dynamically changing) effects of opacity are determining the femtosecond duration of the Xray line emission in contrast to picosecond duration estimated from assumptions of optically thin plasma under steady state conditions [39]. Finally, simulations were carried out for spectra measured from a polished Si wafer to understand the differences in the emission for different morphologies of the samples.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, the ultrashort duration of the generated X-ray emission in relativistic interaction of ultra-high contrast, ultra-short laser pulses with solids is intrinsically related to the transient character of high density plasma. This transient nature of the plasma evolution has to be taken into account when estimating the time scale of radiation cooling processes and determining conditions for new regimes where the plasma cooling caused by plasma self-radiation happens faster than hydrodynamic expansion [39]. High electron density enables ultrafast collisional pumping.…”
Section: Discussionmentioning
confidence: 99%
“…Model simulations also indicate that a further increase in the laser spot size by a factor of 3 would increase the EUV CE by 30 percent. This expected increase in CE is the result of an increase of the plasma hydrodynamic lifetime to radiative lifetime ratio [44].…”
Section: Euv-emitting Source Sizementioning
confidence: 95%
“…Recently, relativistic interaction of ultrashort laser pulses with nano-or micro-structured targets has attracted interest, mainly because of the enhanced efficiency of laser absorption. Depending on the target geometry, the improved laser-target coupling can result in a volumetric heating of the plasma up to extreme temperatures [5], in a more efficient x-ray emission [6] or in an efficient production of HE [7][8][9]. It was shown that for aligned arrays of micropillars or microchannels, the interaction can lead to mega-Ampere currents of relativistic electrons propagating into the target [10], resulting in the self-generation of a mega-Gauss magnetic field on its rear surface [11].…”
Section: Introductionmentioning
confidence: 99%